Intention and practice on personal preventive measures against COVID-19 among older adults in the Kingdom of Saudi Arabia: an epidemiological study using the Theory of Planned Behaviour - AlOmar, Reem S.; AlHarbi, Amal S.; Abu Abdullah, Layla A.; Almuqbil, Sarah M.; Albahrani, Zahra S.; Aldar, Hawra M.; Alzouri, Fatimah S.; Al-Shiban, Manar A.; AlShamlan, Nouf A.; Shafey, Marwa M.; AlAbdulKader, Assim M.; Alotaibi, Nijr S. (Frontiers in Public Health, 2023)
Older adults aged 65 years and above are among the most vulnerable to adverse outcomes and death following a COVID-19 infection. The weekly epidemiological updates by the World Health Organisation show that the continued emergence of concerning subtypes of the virus indicates that the pandemic remains a public health concern and the public should continue to comply with personal preventive measures (PPMs). This study applies the Theory of Planned Behaviour (TPB) which is rooted in the field of Public Health, Epidemiology, and Preventive Medicine to Saudi older adults to predict their health behaviour.This behavioural epidemiological study recruited older adult participants aged 65 years of age and above. A tool which consisted of sociodemographic and health-related questions, as well as questions regarding the components of the TPB, namely, Attitude, Subjective Norm, Perceived Behavioural Control. Bivariate analyses, followed by unadjusted and adjusted multivariable logistic regression analyses were performed to derive odds ratios and 95% confidence intervals.The total number of participants was 502. The mean age was 70.34 years, with similar distributions between males and females. In total, 52.2% intended to practice PPMs, whereas only 48% had a good practice. Also, 56% had a favourable Attitude towards PPMs, 61.4% had a positive Subjective Norm and 39.8% had perceived they had a high control over their behaviour. Females, high educational status were predictors for high intention to practice PPMs (OR = 1.59, 95% CI = 1.01 -2.52 and OR = 2.72, 95% CI = 1.44 -5.16 respectively).Further predictors included Attitudes, Subjective Norm and Perceived Behavioural Control.Results also show that intention to practice was significantly associated with a lower odd of practicing PPMs (OR = 0.06, 95% CI = 0.04 -0.10).Current findings highlight the need to continue with public health efforts targeting vulnerable older adults. Also, the fact that intention negatively predicted practice highlights the need for further behavioural epidemiological studies addressing the intention-behaviour gap.